PENEKANAN PERKEMBANGAN PENYAKIT BUSUK BATANG VANILI (FUSARIUM OXYSPORUM F.SP. VANILLAE) MELALUI SELEKSI ASAM FUSARAT SECARA IN VITRO - Endang Nurcahyani; Issirep Sumardi; Bambang Hadisutrisno; E. Suharyanto (Universitas Lampung, 2012)
The most biological constrain on Vanilla planifolia plantation recently was caused by epidemical disease that laterdecrease vanilla production. The most important disease on vanilla is foot rot disease caused by Fusarium oxysporum f. sp.vanillae. So far, the disease has not been successfully controlled although some experiments had been conducted. Onealternative method has been introduced by using a new cultivar which was resistance to Fusarium). A mutant vanilla to thefungus has been initiated by in vitro selection on medium containing fusaric acid. The aims of this research were: (1) to investigate effective concentration of fusaric acid used for in vitro selection, (2) to characterize mutants which have been set up and also to test those mutants for their resistance to the fungus. The results showed that: (1) fusaric acid at the concentration of 110 ppm effectively suppressed the disease intensity up to 25% compared to the concentration of 90 ppm and 100 ppm. In other words, 110 ppm of fusaric acid has increased the category criterion from moderate to resistant, (2) there was an increase of the total phenol content and thickness of lignin in vanilla stem, and (3) the protein profile of vanilla plantlet was different from the control. There was an initiation of a new band of about 18 kD in a mutant predicted as a protein which is responsible for vanilla resistance to Fusarium.